Neoliberalismo, Estado de derecho y gestión de la corrupción - del Aguila M., Levy (2019)
The corruption of public management systems is a place of recurrent citizen interpellation in Peru. Long historical, the last few years have meant a kind of escalation in the history of corruption, as well as the moment in which the magnitude and depth of public corruption has begun to be known; specifically, for the democratic period that results from the fall of the Fujimorist regime in 2001. The present article proposes that, from the point of view of the Management Sciences, the understanding of this phenomenon demands a proper perspective of the systems complexes to account for the organizational framework in which the phenomenon of corruption takes place. A complex perspective on the issue must begin by addressing the mutual dependence between the corruption of the public and the agency of the private companies that have flourished under its umbrella, which, in turn, have synergistically modeled certain public systems so that they are conveniently disposed to their accumulation interest. Also, from a historical perspective, a way to understand the modernization of the State and, more broadly, the development model in the country, where the priority of capitalist interest on the interest of the common has been patent. Our hypothesis is that, after the Fujimorist regime fell, corruption mutates and manages to adapt to its new conditions of reproduction. Thus, the neoliberal development model endures under the parameters of post- Fujimori democratic State of law. It makes so with a way of understanding and privileging business economic activity to the detriment of the interests of the national community. In this privilege is that corruption finds its place and its systemic opportunity. To address this question, we begin with some general theoretical considerations about the relationship between the private and the public in modern societies. In the second place, we have characterized the knot of our question about the installation of the liberal-democratic regime in Peru from 2001 to the present, to argue that corruption was able to come together and find its occasion under legal and public management structures perfectly installed in the democratic State of law. Then, the Odebrecht case will be used to illustrate in a tangible way the scope and depth that corruption has achieved in the country. Finally, we will raise some reflections on the practical challenges of dealing with this phenomenon with radicalism, questioning the development model and the current way in which modernization of the State operates, as well as on the cognitive challenges that this means for Management Sciences.